The Use of Study Anxiety Intervention in Reducing Anxiety to Improve Academic Performance among University Students - Mohd Ghani, Awang; Muhammad Nubli, Abdul Wahab; Ahmad, Othman; Prima, Vitasari (Canadian Center of Science and Education, 2010)
Anxiety is one of the wide varieties of emotional and behaviour disorders, it is a major predictor for low academic performance among students. To this, anxiety should be taken seriously. Students need some form of intervention to reduce anxiety and assist in improving academic performance. Study anxiety intervention is designed to help students handle the problem of anxiety while studying. In this paper, a study anxiety intervention program is designed to manage students study anxiety in order to improve academic performance among students is proposed. Twelve healthy students are selected for this research, from five engineering faculties at Universiti Malaysia Pahang. They are divided into two equal groups which the experiment group and the control group, each are six participants. The training runs on duration of six sessions with the experiment groups receiving full training and no training for the control groups. The results show that the experiment groups performed better in coping anxiety levels as well as increasing academic performance compared to the control groups. Based on these results, study anxiety intervention can be concluded as an effective program to improve academic performance among university students. Therefore, the participants should practice these techniques effectively to be able in study anxiety coping to enhance their academic performance.